Integrating Psychoneuroimmunology into Wound Healing: A Systematic Review on the Role of Mind-Body Interventions in Nursing Practice - Ismayadi Ismayadi; Alisarjuni Padang (International Forum of Researchers and Lecturers, 2025)
This systematic literature review explores the role of psychoneuroimmunology (PNI)-based mind-body interventions in improving wound healing within nursing practice. Wound healing is a complex, multifactorial process influenced not only by cellular and molecular factors but also by psychological and immune responses. Despite the growing body of evidence supporting the efficacy of mind-body practices such as guided imagery, hypnotherapy, and meditation in managing stress and modulating immune responses, there is limited integration of these interventions into clinical nursing practices. This review aims to bridge this gap by synthesizing studies published between 2020 and 2024 that examine the impact of these interventions on wound healing outcomes. The review follows the PRISMA protocol, analyzing data from 50 primary studies focusing on RCTs, systematic reviews, and quasi-experimental designs. The results show significant improvements in wound closure rates, pain reduction, and immune modulation (e.g., reduction in cortisol and pro-inflammatory cytokines) in patients who received mind-body interventions. The findings support the hypothesis that mind-body interventions, by addressing both psychological stress and immune function, enhance wound healing. The proposed framework for integrating PNI-based interventions into nursing practice could improve patient outcomes in chronic wound management. Future research should focus on long-term studies with larger sample sizes and standardized intervention protocols to further validate these findings.